MAMPUKAH INDONESIA BERSEPAKAT UNTUK MELAKUKAN PENINGKATAN SUMBERDAYA MANUSIA (SDM) YANG CERDAS DAN BERKUALITAS - ., Atmarita (PERSATUAN AHLI GIZI INDONESIA, 2006)
Malnutrition remains widespread and serious in Indonesia. It is almost halve of the Indonesian population suffer from several malnutrition forms and nearly 40% preschool children are stunted. Malnutrition influences a huge economic burden, investing in nutrition program is important for human development. However, Indonesia seems investing nutrition only as an intervention in health, agriculture, or social protection and not as an outcome measure of development. Nutrition is one of the most sensitive overall measures of poverty reduction, where this is defined as improving human development. This article analyzed secondary available data from National SocioEconomic Survey (SUSENAS) to present the evidence of missing opportunity in human development improvement program indicated by nutrition situation stays at the same figures even the prevalence of underweight tend to increased for the last 5 years. The assessment also showed that politically the government has committed to give more money to nutrition; however this commitment should be followed by bringing the involved stakeholders on nutrition to improve the quality of intervention in order to reach the targeted impact. It is recommended that Indonesia should start preparing complete information for reviewing strategy that will benefit to the community, provide policy analysis, as well as improving program management.